From Fundamental Research to the Design of a Software Solution to Help Poor Readers. (April 2020) - Ecalle, Jean; Vidalenc, Jean-Luc; Ballet, Carine; Magnan, Annie
Fundamental research has indicated that (a) difficulties in reading are linked to a deficit in phonemic awareness and word reading and (b) in French, decoding and word reading are based on the syllable as a functional unit. A software program involving two tasks, namely, phonemic discrimination and grapho-syllabic segmentation, was proposed to poor readers aged from 7 to 12 years in order to stimulate their reading skills. Two experiments were set up during which the children were trained for a total of 10 hours. In Experiment 1, conducted at home, we observed meaningful progress in phonemic awareness and decoding after training only in the poorest readers. In Experiment 2, which was conducted at school, we observed significant short- and medium-term effects on phonemic awareness, decoding, and word reading. These encouraging results support the use of evidence-based practices based on tools validated by means of experimental research in ecological situations.